Analysis of credit risk, liquidity and profitability of the Trade Bank of Iraq for the period (2012-2021) - Abdulhassan Abbas, Ali; Amjed Jawad, Dhay (Technium Business and Management, 2023)
Recently, the global recurrent and diverse crises have increased, and the risks have increased significantly, including the credit risks to the banking sector, and thus the bank has incurred large losses that have an impact on liquidity and profitability. Credit risks may lead to bank's bankruptcy or failure. This research attempts to find the relationship between credit risk, liquidity and profitability together. The data for the Commercial Bank of Iraq were used for a period of ten years. One of the most important objectives of the research is the bank credit, which has a major role in the process of economic development and direct economic activity towards development projects and investment of its accumulated deposits and provide interest for these deposits, and it was concluded that the bank should diversify its investments and increase the granting of loans in foreign currency. Financial restructuring and re-pricing of its shares and the trend in speculation in global markets, and to have investments in the shares of solid international companies to achieve financial flows within it for its balance sheet.